Design of Web-Based Hydroponic Plant’s Room Temperature and Water Nutrition Monitoring System - Rismayani Rismayani; Hasyrif SY (Jurnal Pekommas, 2020)
Hydroponics is a technique of cultivation that uses water and without soil. The technique emphasizes meeting the nutritional needs of plants. Hydroponic plants need less water than plants that use soil media. The purpose of this study is the creation of a monitoring system to control room temperature and hydroponic water plant nutrition. The method used is web-based system design. The results of the study show that with a web-based room temperature and water nutrition monitoring system, room temperature and water nutrition of the hydroponic plant can be controlled anytime and anywhere. Also, test factors in functional testing of systems using black-box show valid results. Furthermore, based on the implementation test conducted to determine the performance of the monitoring system that has been made, 87.5% of 35 respondents rated it good, 9% thought it was quite good, and 3.5% thought it was not good.